Aerodynamic validation of rFlow3D code with UH-60A data including high advance ratios - Tanabe, Y.; Suguwara, H. (My University, 2015)
Validation of the rFlow3D code developed at Japan Aerospace Exploration Agency (JAXA) has been carried out with the published UH-60A test data in hover and forward flight. Also, the slowed rotor conditions are simulated to investigate the applicability of this code at high advance ratios. Although the elastic deformation of the blade is not considered at this point, good agreement of the aerodynamic performance is obtained compared with the experimental data. Extensions of the CFD solver toward complete compound helicopter simulations are also discussed.
Keywords: Aerodynamics